Loan portfolio structures, risk and performance of different bank ownership types: An Indonesian case - Atahau, Apriani Dorkas Rambu (Curtin University, 2014)
This study examine the loan portfolio structures, risk and performance of different bank ownership types in Indonesia over the period 2003-2011. Financial data of the banks are analysed by applying non-parametric univariate statistics and regression analysis. This research finds significant changes and differences between the loan portfolio structures and performance of the different bank ownership types. The findings enable the Central Bank of Indonesia to consider the ownership differences when developing or changing credit regulations.